PENGARUH INSTAGRAM SEBAGAI MEDIA EDUKASI TERHADAP PENGETAHUAN DAN SIKAP TENTANG ANEMIA PADA REMAJA PUTRI - Imelda Cahya Aprilia; Nana Usnawati; Dwi Purwanti; Siti Alfiah (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Adolescence is an important period for growth and development related to the start of puberty. This research was a quantitative type with a Quasi Experimental design with Nonequivalent Control Group Design. Population 96 female students. Sample of 33 female students SMK Satya Widya Surabaya with Simple Random Sampling. The independent variable is the educational media Instagram, the dependent variable is teenagers' knowledge and attitudes about anemia in young women. The instrument is a questionnaire. Analysis of the influence of the Wilcoxon Signed Rank Test. The results of the research after being given the intervention were that almost all respondents had good knowledge (90.9%). After being given the intervention, all respondents were positive (100%). The results of the Wilcoxon Sign Rank Test showed an influence before and after the intervention using Instagram on the knowledge and attitudes of young women about anemia. Test results Man Whitney there are differences before and after the intervention using Instagram on the knowledge and attitudes of young women about anemia. Inconclusion, there is the influence of Instagram as an educational medium on the knowledge and attitudes of young women about anemia at SMK Satya Widya Surabaya.